Four views on hell - Crockett, William V. (Grand Rapids, Mich. : Zondervan Publishing, 1996)
Is hell to be understood literally as a place of eternal smoke and flames? Or are such images simply metaphors for a real but different form of punishment? Is there such a thing as "conditional immortality," in which God annihilates the souls of the wicked rather than punishing them endlessly? Is there a Purgatory, and if so, how does it fit into the picture? The interactive Counterpoints forum allows the reader to see the four views on hell--literal, metaphorical, conditional, and purgatorial--in interaction with each other. Each view in turn is presented, critiqued, and defended. --From publisher's description.
The literal view / John W. Walvoord -- The metaphorical view / William V. Crockett -- The purgatorial view / Zachary J. Hayes -- The conditional view / Clark H. Pinnock.
Originally published: Grand Rapids, Mich. : Zondervan, 1992.
Includes bibliographical references and indexes.
Keywords: Hell -- Christianity; Hell -- Christianity